The influence of supplier development, in the form of contract farming, on performance in Zimbabwean tobacco industry - Imtiaz Alam; Jugindar Singh Kartar Singh; Muhammad Umar Islam (Cogent Business & Management, 2021)
Supplier development in the farming industry takes the form of contract farming. Contract farming was introduced to tobacco farming in 2004. Prior to that contract farming has been thriving in other crops such as cotton and sugarcane. Previous studies on tobacco farming had an unbalanced focus on the social aspects of contract farming thereby largely neglecting the economic benefits of the same phenomenon. This study therefore seeks to determine how supplier development in the form of contract farming impact on supplier performances. A survey of 20 tobacco firms who had to rate 400 farmers was conducted, and the findings indicated that contract farming leads to improved cost performance and quality performance. However, the study recorded no statistically significant effects of contract farming on delivery performance. It was therefore recommended that contract farming structures must be strengthened in order to reap on the achieved benefits in terms of improved cost performance and quality performance.
Keywords: 650; Ethical leadership; employee engagement; organisational commitment; perceived supervisor support